Implementasi Pendidikan Karakter Berbasis Toleransi dalam Pembentukan Sikap Pluralisme - Aliyah, Sofiatil; Zubaidi, Ahmad; Machfudi, Moch. Imam; Wahono, Suparwoto Sapto; Arifin, Miftah (Lembaga Riset dan Inovasi Almatani, 2025)
This study examines the implementation of tolerance-based character education in shaping pluralistic attitudes among students at Pondok Pesantren Nurul Jadid, Paiton Probolinggo. Using a qualitative case study approach, the research explores the mechanisms of habituation, exemplary leadership, and value integration within the curriculum and religious activities. Data were collected through interviews, observations, and documentation involving pesantren leaders, teachers, student organizations, and senior students. The findings reveal that daily interactions in the pesantren—structured around the Panca Kesadaran Santri (Five Awarenesses of Students): religious awareness, intellectual awareness, social awareness, national awareness, and organizational awareness—serve as the foundation for internalizing tolerance values. Tolerance is cultivated through positive social contact in shared spaces, conflict resolution guided by educators, and dialogical learning forums such as halaqah, bahtsul masail, and comparative fiqh studies. These processes contribute significantly to the development of pluralistic attitudes in cognitive, affective, and conative dimensions. The study concludes that pesantren plays a strategic role as a socialization space for moderation, producing students who are inclusive, adaptive, and capable of living harmoniously within a diverse society.